Opportunities for innovation in maize hybrid seed products: Insights from Guatemala and El Salvador - Peña, Meliza; Donovan, Jason; Rutsaert, Pieter (CGIAR System Organization, 2025)
Across Central America, dozens of locally owned small and medium-scale maize enterprises (maize SMEs) have emerged in the past few decades, which now represent a critical source of hybrid maize seed for small-scale farmers. Typically, these enterprises acquire foundation seed from public breeding programs, which they then multiply, process, and package, to sell to government agencies and NGOs. The future growth prospects of these maize SMEs depends, in part, on their ability to launch new seed products and diversify their marketing channels to include sales to retailers. This brief explores demand-side opportunities for new maize hybrids in Guatemala and El Salvador. We conducted 27 interviews, including with 10 maize SMEs (six in Guatemala and four in El Salvador), and triangulated the information with national agricultural research and extension systems, international seed companies, and seed retailers. Our study identified the requirements for maize products related to end-use (e.g., green maize1 and silage), processing (e.g., maize for the snack industry and blue maize for restaurants and processors), and production (e.g., shorter maturity cycles). Maize SMEs recognized the potential future shift toward early-maturity products if the tendency for the delayed onset of the rainy season continues.